Concerted Ion Migration and Diffusion‐Induced Degradation in Lead‐Free Ag3BiI6 Rudorffite Solar Cells under Ambient Conditions. Issue 8 (8th July 2021) - Kulkarni, Ashish; Ünlü, Feray; Pant, Namrata; Kaur, Jagjit; Bohr, Christoph; Jena, Ajay Kumar; Öz, Senol; Yanagida, Masatoshi; Shirai, Yasuhiro; Ikegami, Masashi; Miyano, Kenjiro; Tachibana, Yasuhiro; et al.
Abstract : Silver bismuth iodide (SBI) materials have recently gained attention as nontoxic alternatives to lead perovskites. Although most of the studies have been focusing on photovoltaic performance, the inherent ionic nature of SBI materials, their diffusive behavior, and influence on material/device stability is underexplored. Herein, AgBi2 I7, Ag2 BiI5, and Ag3 BiI6 thin films are developed in controlled ambient humidity conditions with a decent efficiency up to 2.32%. While exploring the device stability, it is found that Ag3 BiI6 exhibits a unique ion‐migration behavior where Ag +, Bi 3+, and I − ions migrate and diffuse through the dopant‐free hole transport layer (HTL) leading to degradation. Interestingly, this ion‐migration behavior is relatively fast for the case of antisolvent‐processed Ag3 BiI6 thin‐film‐based devices contrasting the case of without antisolvent and is not observed for other SBI material‐based devices. Theoretical calculations suggest that low decomposition enthalpy favors the decomposition of Ag3 BiI6 to AgI and BiI3 causing migration of ions to the electrode which is protected by using a thick HTL . The new mechanism reported herein underlines the importance of SBI material composition and fundamental mechanism understanding on the stability of Ag3 BiI6 material for better solar cell design and also in extending the applications of unique ion‐migration behavior in various optoelectronics. Abstract : Herein, a unique triple‐ion migration phenomenon in Ag3 BiI6 solar cells is reported. Under ambient atmosphere, Ag +, Bi 3+, and I − ions migrate and decompose the metal electrode leading to performance degradation. This study highlights the importance of understanding the Ag3 BiI6 material for better solar cell design and also stimulates the use of this unique ion‐migration behavior in other optoelectronics.